Simultaneous Quantification of Six Bioactive Components in Decoction of Ziziphi spinosae Semen Using Ultrahigh Performance Liquid Chromatography Coupled with Triple-Quadrupole Mass Spectrometry - Xiao Liu; Xiaochai Zhu; Hui Zhu; Li Xie; Jia Ma; Yinghui Xu; Qigang Zhou; Zejun Wu; Baochang Cai (Journal of Analytical Methods in Chemistry)
This paper was conducted to develop a method containing ultrahigh performance liquid chromatography coupled with triple-quadrupole tandem mass spectrometry for simultaneous quantification of six bioactive components in the decoction of Ziziphi spinosae Semen. Analysis was performed on an Agilent ZORBAX Extend-C18 column (2.1 × 100 mm, 1.8 μm) and eluted with a mobile phase system consisting of acetonitrile and water under a gradient program with a flow rate of 0.3 ml/min. The injection volume was 2 μl. Multiple-reaction monitoring scanning detection was employed for quantification with an electrospray ion source in the negative ion mode. All the six compounds showed good linearities (r≥0.9996). The LODs of the six bioactive compounds were 0.039 ng/ml, 0.092 ng/ml, 3.112 ng/ml, 2.131 ng/ml, 0.099 ng/ml, and 0.071 ng/ml for spinosin, 6‴-feruloylspinosin, jujuboside A, jujuboside B, camelliaside B, and betulinic acid, respectively. The LOQs were 0.118 ng/ml, 0.276 ng/ml, 9.336 ng/ml, 6.393 ng/ml, 0.299 ng/ml, and 0.213 ng/ml for spinosin, 6‴-feruloylspinosin, jujuboside A, jujuboside B, camelliaside B, and betulinic acid, respectively. According to our knowledge, it was the first time to establish a method with high efficiency and accuracy for the quantification of six bioactive components in the decoction of Ziziphi spinosae Semen, which would provide references for quality control and evaluation of Ziziphi spinosae Semen.